Emerging Market Small and Medium Enterprises Internationalisation: A Meta-Analysis - Kong, Linglong (Auckland University of Technology, 2018)
The literature on firm internationalisation has traditionally focused on MNCs (Multinational Corporations), often from the perspective of developed markets. However, recent research has examined the role of SMEs within developed markets, MNCs from emerging markets, and recently began to acknowledge the important role which emerging market SMEs have. It is important to study emerging market SMEs since they play an important role in a country’s economic development especially in emerging markets. The literature on emerging market SMEs and their internationalisation behaviours and performance is underdeveloped, and large-scale quantitative studies are rare. The aim of this research is to study the extant literature to highlight where there is agreement or debate on emerging market SMEs internationalisation. A qualitative meta-analysis approach has been employed to examine themes within the literature. As the literature had insufficient comparable studies to perform a quantitative meta-analysis, a qualitative meta-analysis was employed, which is particularly suited to highlighting themes. 460 journals were systematically searched from ABDC (Australia Business Deans Council) Journal Quality List 2016 to identify relevant research, which was screened for robustness, in the end resulted in 64 articles being selected as the research data. By systematically reviewing these articles, seven common emerging market SMEs internationalisation processes are highlighted, they are: 1) Influence-based; 2) Ambidexterity; 3) Springboard effect acquisition; 4) Wholly-owned subsidiaries or joint ventures; 5) Product-copying; 6) Networks and alliances (including social ties and agencies); and 7) Location-focus. Four common emerging market SMEs internationalisation barriers and challenges are also derived from the literature, they are: 1) Political barriers; 2) Cultural distance; 3) Organizational incapability and slow integration; and 4) Poor leadership. Finally, four common characteristics of emerging market SMEs are highlighted as well, they are: 1) Family controlled/owned; 2) Early internationalisation; 3) Highly established social ties and networks; and 4) Poor brand recognition and loyalty. Findings suggested that emerging market SMEs internationalisation are only partially different than emerging market MNCs or developed market firm internationalisation. However, the differences are significant which indicates that emerging market SMEs deserve more standalone, large-scale research. This dissertation contributed to the current EM SMEs internationalisation literature by providing an overall understanding of the current literature agreements. This collective understanding could be used to detect and plan for future research directions. This dissertation also highlighted several successful EM SMEs internationalisation patterns consisted of process, barrier and characteristic, which could be employed by EM SMEs managers or owners during internationalisation.
Keywords: internationalisation; SMEs; Emerging market; Meta-analysis